CHALLENGES AND OPPORTUNITIES OF MANAGEMENT INFORMATION SYSTEM (MIS) IMPLEMENTATION IN ISLAMIC EDUCATION INSTITUTIONS - Bahrul Mu'min, Muh.; S. Nugraha, Mulyawan (As-Sulthan Journal of Education, 2024)
The implementation of Management Information Systems (MIS) in Islamic educational institutions serves as a crucial strategy to enhance administrative efficiency, transparency, and the quality of educational services. However, this implementation process faces various challenges, including limited human resources, technological infrastructure, and resistance to change. This study aims to identify the challenges and opportunities in implementing MIS in Islamic educational institutions through a qualitative approach based on literature studies. Data were collected from various journal articles, books, and relevant official documents. The findings reveal that despite certain challenges, significant opportunities arise from government support, increasingly affordable technology, and the demand for modernizing educational management. This study provides recommendations to strengthen human resource capacity, expand infrastructure, and integrate MIS into the strategic policies of Islamic educational institutions. These findings are expected to assist policymakers and practitioners in optimizing MIS implementation to enhance the competitiveness of Islamic educational institutions.